PERLINDUNGAN DAN PELAYANAN JASA NOTARIS TERHADAP MASYARAKAT TIDAK MAMPU - Agustinus Andy Toryanto (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2008)
Change of paradigm of Notary in Indonesia start form with its Act No. 30/2004. One of important matter the carried the make-up of role of profession organization in arranging behavior of Notary for the shake of is harmonious of relation between Notary and also in giving service to society unable to Result of research indicate that not yet entirely Notary in Central Provinsi of Java give service to indigent society relate to contribution of expense of made akte. Notary tend to to specify of is expense of pursuant to order specified by Grouping organization of Notary Indonesia. Disinclination give service in the form of Liberation of expense, even meant as indisposed emulation effort. In the effort giving protection of service and law to society unable to, hence needing harmonisasi arrangement of service to society unable to be specified expressly in the form of regulation of invitation having the character of to fasten and give certainty of service by Notary.